Leukemia Cutis as an Early Presentation or Relapsing Manifestation of Chronic Lymphocytic Leukemia (CLL): Leukemia Cutis in Chronic Lymphocytic Leukemia - Aldapt, Mahmood B.; Yassin, Mohamed (Acta Biomedica Atenei Parmensis, 2021)
Background and Objective: Cutaneous infiltration by Chronic Lymphocytic Leukemia (CLL) is a rare complication. The clinical presentation, impact of it on disease prognosis, and the proper treatment choice are not clear. Here in our review, we try to answer these questions. Acquisition of evidences: A systematic search of PubMed, and Google Scholar for English language articles published from Jan 2000 to June 2019. Synthesis of evidences: A total of 56 cases were identified, with a median age of 66 years. Of these cases 43 were males and 12 were females, and one missing data, with a ratio of 3,6:1. Head and neck were most commonly involved. The commonest clinical presentation was papulonodular lesions, and the majority were diagnosed at an early stage. CLL skin involvement at the site of old herpetic lesions was common. Because of the rarity of the disease, treatment modalities varied widely, and there are no consensus on treatment. The majority were treated with chemotherapy. In general, 35 (77.8% - of the non-missing data) patients responded to treatment (25 patients had a complete remission and 10 a partial remission). All patients ≤60 years had an early-stage disease, on the other hand, all patients with advanced-stage were >60 years. Conclusion: Patients with early-stage and localized leukemia cutis can benefit from observation alone strategy, while intervention in young patients with advanced disease is warranted. Skin infiltration by CLL does not affect prognosis, as most patients attained complete or partial remission with a very low progression rate.